Smart Cities Governance: The Need for a Holistic Approach to Assessing Urban Participatory Policy Making. (December 2016) - Castelnovo, Walter; Misuraca, Gianluca; Savoldelli, Alberto
Most of the definitions of a "smart city" make a direct or indirect reference to improving performance as one of the main objectives of initiatives to make cities "smarter". Several evaluation approaches and models have been put forward in literature and practice to measure smart cities. However, they are often normative or limited to certain aspects of cities' "smartness", and a more comprehensive and holistic approach seems to be lacking. Thus, building on a review of the literature and practice in the field, this paper aims to discuss the importance of adopting a holistic approach to the assessment of smart city governance and policy decision making. It also proposes a performance assessment framework that overcomes the limitations of existing approaches and contributes to filling the current gap in the knowledge base in this domain. One of the innovative elements of the proposed framework is its holistic approach to policy evaluation. It is designed to address a smart city's specificities and can benefit from the active participation of citizens in assessing the public value of policy decisions and their sustainability over time. We focus our attention on the performance measurement of codesign and coproduction by stakeholders and social innovation processes related to public value generation. More specifically, we are interested in the assessment of both the citizen centricity of smart city decision making and the processes by which public decisions are implemented, monitored, and evaluated as regards their capability to develop truly "blended" value services—that is, simultaneously socially inclusive, environmentally friendly, and economically sustainable.